2019
DOI: 10.20473/jhpr.vol.2-issue.1.1-5
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Halal and Thayyib and Its Implementation in Indonesia

Abstract: The issue of halal and haram is regarded by Muslims as the basis concept. The word halal is derived from Arabic word, permissibility (in the sense of what is permitted in the Shariah). For Muslims, the basis of every action must be worship, which is worshipping to God Almighty. The eating activity is also a means of worship with rules and procedures according to the Sharia. The Holy Quran says eating is not just enough for halal but it should be thayyib. Therefore, the guarantee of halal products is important.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 2 publications
0
18
0
4
Order By: Relevance
“…Furthermore, research (Shahnaz & Wahyono, 2016) shows that reputation and trust variables have a positive and significant effect on purchase intention. In addition, other research results show that the variables of halal certification, food ingredients and purchase intention have a significant effect on purchasing decisions (Nafis, 2019). This study aims to classify the characteristics of Muslim students as consumers of halal culinary tourism in Sidoarjo Regency.…”
Section: B Literature Review 1 Halal Culinary Tourismmentioning
confidence: 99%
“…Furthermore, research (Shahnaz & Wahyono, 2016) shows that reputation and trust variables have a positive and significant effect on purchase intention. In addition, other research results show that the variables of halal certification, food ingredients and purchase intention have a significant effect on purchasing decisions (Nafis, 2019). This study aims to classify the characteristics of Muslim students as consumers of halal culinary tourism in Sidoarjo Regency.…”
Section: B Literature Review 1 Halal Culinary Tourismmentioning
confidence: 99%
“…There were studies concerning the development of halal regulations (Akim et al, 2019;Asa, 2019), its implementation (Anwar, Fahrullah, & Ridlwan, 2018;Nafis, 2019;Othman, Shaarani, & Bahron, 2016;Zulkifli & Mochammad Sahid, 2018), and its organizations (Afroniyati, 2014;Faidah, 2017), as well as problems in certification (Prabowo, Rahman, Rahman, & Samah, 2015;Viverita & Kusumastuti, 2017). Except Afroniyati and Faidah's study, the studies have not revealed the inter-organizational relations after the enactment of the Act No.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It means that not all halal foods are good. According to Al-Saadi on Tayseer Al-Kareem from Al-Baqarah 168 that it calls all human beings, believers and non-believers [5]. Likewise, Halal concept in Islam involves quality product consumed, such as hygiene, cleanliness, management to enhance good food from a good process.…”
Section: Halal Food Industry In Thailandmentioning
confidence: 99%